2022
DOI: 10.1371/journal.pone.0278244
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the association between stigma and HIV status and fertility intention by fertility desire among heterosexual couples living with HIV in Kunming, China

Abstract: Objectives This study aimed to assess the influences of stigma and HIV status on reproductive intention among heterosexual couples living with HIV in China. Methods A cross-sectional study was conducted in Kunming, China among 315 HIV-positive individuals and their spouses (n = 315 couples). An interview questionnaire was used to collect data on intention, desire, HIV Stigma Scale items, and HIV status. Dyadic fertility intention was examined using the actor-partner interdependence mediation model, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Under these circumstances, the impact of HIV on crucial life milestones can significantly influence the decision-making process for PWH. They may face uncertainties when making important life choices, such as whether to get married and have children (Gigstad et al, 2023; Guo et al, 2022); whether to disclose their HIV status to friends, family, sexual partners, and others (Yang et al, 2023); and whether to change jobs or avoid jobs with HIV testing involved in pre-employment or annual medical examination (Celeste-Villalvir et al, 2023). Effective appraisal support requires that support providers not influence PWH's decision-making with personal subjective tendencies and preferences.…”
Section: Appraisal Supportmentioning
confidence: 99%
“…Under these circumstances, the impact of HIV on crucial life milestones can significantly influence the decision-making process for PWH. They may face uncertainties when making important life choices, such as whether to get married and have children (Gigstad et al, 2023; Guo et al, 2022); whether to disclose their HIV status to friends, family, sexual partners, and others (Yang et al, 2023); and whether to change jobs or avoid jobs with HIV testing involved in pre-employment or annual medical examination (Celeste-Villalvir et al, 2023). Effective appraisal support requires that support providers not influence PWH's decision-making with personal subjective tendencies and preferences.…”
Section: Appraisal Supportmentioning
confidence: 99%
“… 25 The previous studies used a dyadic approach to assess the fertility desire and intention by other factors such as stigma, HIV status, HIV-related worriers and living children. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…25 The previous studies used a dyadic approach to assess the fertility desire and intention by other factors such as stigma, HIV status, HIV-related worriers and living children. 26,27 The objective of the current study was to document the effects of (in)congruency in fertility motivation linked to intention via desire among CLWH using the APIM and DRSA. To achieve this objective, we divided the analysis into three parts: the causal pathway; degree of husband-wife congruence of fertility motivations; and congruency effect of fertility motivation between wives and husbands on fertility desire/intention.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there are various studies that relate the TDIB model to various variables such as politics (Liu et al, 2023), fatal diseases (Buber-Ennser et al, 2023;Djiometio et al, 2019;Guo et al, 2022), race (Alexander et al, 2021), couple relationship (Barber et al, 2019), among others; empirical evidence of family of origin characteristics as predictors of CM in the national and international literature is scarce (Rich et al, 2021;Varas & Borsa, 2021). Gerson (1980Gerson ( , 1983Gerson ( , 1984Gerson ( , 1986, assessed the impact on CM of perceived parental attention, parental identification, and happiness of family life in childhood and the results indicated that CMs are correlated with the aforementioned variables.…”
mentioning
confidence: 99%